The Evolution Characteristics and Enhancement Paths of the Economy-Society-Ecology Coordinated Development Level of Changsha-Zhuzhou-Xiangtan Urban Agglomeration - Chen Yizhang; Zhou Guohua; Wang Hua; Cui Shuqiang; Bi Fangze; Yu Xuexia (Redai dili, 2023)
Promoting the coordinated development of urban agglomerations is a fundamental goal in new urbanization construction in China. It is an inherent requirement for condensing the joint efforts of various cities, and a primary path to maximizing the overall benefits and enhancing the competitiveness of urban agglomerations. Based on the composite system synergy degree model, this study analyzes urban agglomeration as a composite system integrated with the economy, society, and ecology subsystems. Using evidence from the Changsha-Zhuzhou-Xiangtan urban agglomeration, we research the evolutionary characteristics of its coordinated development level since the resource-saving and environment-friendly development experimental area was established. We also explore the improvement path of optimizing the coordinated development of urban agglomerations. The results show that from 2007 to 2019: 1) at the urban agglomeration scale, the order degree of economy, society, and ecology subsystems in the Changsha-Zhuzhou-Xiangtan urban agglomeration displays an overall improvement trend, and the synergy degree of the composite system changed from mild imbalance to moderate synergy; 2) at the urban scale, Changsha and Zhuzhou have achieved moderate synergy, while Xiangtan remains at mild synergy; the synergy degree of the composite system in Changsha continues to strengthen, and those in Zhuzhou and Xiangtan are relatively weakened; 3) the two main problems in the coordinated development are that the coordinated level is low, and the socio-ecological subsystem changes slowly with the main infrastructure and environmental governance constraints. In addition, there are obvious gaps in the level of coordination between cities, with constraints in the economic scale, development quality, industrial structure, and pollution emissions; and 4) to further improve the level of coordinated development of the Changsha-Zhuzhou-Xiangtan urban agglomeration, it is necessary to reasonably formulate the orderly development and coordinate the goals of various subsystems at the scale of the urban agglomeration. It is also necessary to improve the overall management mechanism of finance and public affairs. At the urban scale, cities should make up for their shortcomings, improve their development level, and continuously improve the interaction and cooperation mechanism between cities. The primary contributions of this paper are to add to the discussion on the interactive relationship between the economic, social, and ecological dimensions of urban agglomerations, as well as propose targeted improvement paths to provide certain experiences for the Changsha-Zhuzhou-Xiangtan Urban Agglomeration and other urban agglomerations in China to improve their collaborative development ability.